Can an 'automatic antimicrobials stop policy' be safely introduced to 'paediatric wards' to prevent prolonged courses of treatment?. Issue 5 (22nd April 2012) - Adeniji, F; Christiansen, N; Lo, A
Abstract : Objectives: The aim is to prevent inappropriate prolonged courses of antimicrobials, minimise wastage of antimicrobials and promote good prescribing practice of antimicrobials through achieving the following objectives: ▶ Improving compliance with the key performance indicators (KPIs) for prescribing antimicrobials at Barts and The London NHS Trust. ▶ Implementing an antimicrobial review date policy on paediatric wards. Method: The features and implementation of the policy were as follows: ▶ When a prescribed antimicrobial agent did not comply with the Trust KPIs for antimicrobial prescribing, the ward pharmacist would query this using a preprinted antimicrobial KPI green sticker in the notes (ideally within 48 h of the prescription). ▶ Where there was no intended duration of therapy or review date on the drug chart, an automatic stop sticker was placed on the chart for the antimicrobial to stop after 5 days of treatment (with specific exclusions which included haematology oncology patients, patients with infections requiring long treatment courses for example, in cystic fibrosis and those being treated for neutropenic sepsis). ▶ The prescriber had approximately 72 h to rewrite the prescription if they wished to continue for a different duration. Where a stop date coincided with the weekend or bank holiday the duration was extended to the next normal working day. The automatic antimicrobial stop policy was successfully piloted on a paediatric general medical ward over 5 weeks prior to implementing the policy across the paediatric directorate. Details of the pilot results and policy were emailed to all clinicians, ward managers and the paediatric pharmacy team. The paediatric pharmacy team and senior sisters were trained on the policy including the roles and responsibilities of the doctor, nurse and pharmacist. The policy was introduced to a single ward each week across all the eight paediatric wards including paediatric intensive care and the neonatal unit. Results: 3 monthly KPI snap shot audits conducted by pharmacy as per Trust policy in December showed there was much room for improvement as only 8% of prescriptions specified a review date. However, the last audit which took place during the course of the pilot showed a significant improvement as 47% of prescriptions specified a review date or duration of treatment. Audit results post introduction of the new antimicrobial policy to the whole paediatric directorate are being awaited. Conclusion: Preliminary results have indicated a significant improvement in antimicrobial prescribing in relation to specifying course durations or review dates across the whole paediatric directorate, however further data is currently being awaited.